STRATEGI GURU DALAM PENGEMBANGAN BAKAT DAN MINAT PESERTA DIDIK SD NEGERI 1 LAMBHEU KABUPATEN ACEH BESAR - Nadira Suriani; Intan Safiah; Aida Fitri (Jurnal Binagogik, 2025)
Developing students' talents and interests at the elementary school level is an important part of creating quality and character graduates. This study aims to describe the strategies of class teachers in developing students' talents and interests at SD Negeri 1 Lambheu, as well as identifying supporting and inhibiting factors in its implementation. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the development strategy is carried out comprehensively and adaptively, including through informal identification of student personalities, selection of flexible and interest-based learning systems, application of learning methods and techniques that suit student characters, and determination of clear success criteria. The learning approach is participatory and humanistic, which allows students to express their potential comfortably and naturally. Supporting factors in the implementation of this strategy include student enthusiasm, active teacher involvement, principal support, and collaboration with parents. On the other hand, the obstacles faced include limited supporting facilities for activities, a tight academic schedule, and low understanding of some parents regarding the importance of non-academic activities. This study recommends that schools improve facilities and infrastructure, adjust learning schedules, strengthen communication with parents, and develop a reward system and cooperation with external parties. With the right strategy and adequate support, the development of students' talents and interests can be carried out optimally and sustainably.